Development, characterization, and deployment of a high-resolution time-of-flight chemical ionization mass spectrometer (HR-TOF-CIMS) for the detection of carboxylic acids and trace-gas species in the troposphere - Brophy, Patrick M., author; Farmer, Delphine, advisor; Bernstein, Elliot R., committee member; McNaughton, Brian, committee member; Pierce, Jeffrey R., committee member; Ravishankara, Akkihebbal R., committee member (Colorado State University. Libraries, 2016)
A historical account of the advances leading to modern high-resolution time-of-flight chemical ionization mass spectrometers (HR-TOF-CIMS) for gas-phase measurements is presented. Recent literature detailing the description of the HR-TOF-CIMS is critically evaluated and put into the context of the historical literature. The development of the HR-TOF-CIMS with reagent ion switching capabilities in the negative mode (acetate and iodide reagent ions), and a novel, low-pressure high-flow inlet with online calibration system is shown to work well in the field. Findings from the deployment of this measurement system during the 2013 Southern Oxidant and Aerosol Study are discussed. Subsequent work with voltage scanning methodologies for controlling cluster transmission is presented and applied to potential aerosol mass chamber experiments examining the oxidation of alpha-pinene. The applicability of acetate chemical ionization to the direct headspace analysis of beer samples is presented. Lastly, the future directions of acetate chemical ionization and voltage scanning are discussed in relation to numerous recent developments related to both gas-phase measurements and new particle formation.
Keywords: carboxylic acids; field measurements; acetate CIMS; mass spectrometry; chemical ionization